Antibody persistence and neutralising activity in primary school students and staff: Prospective active surveillance, June to December 2020, England. (November 2021) - Ireland, Georgina; Jeffery-Smith, Anna; Zambon, Maria; Hoschler, Katja; Harris, Ross; Poh, John; Baawuah, Frances; Beckmann, Joanne; Okike, Ifeanyichukwu O; Ahmad, Shazaad; Garstang, Joanna; Brent, Andrew J; et al.
Abstract: Background: Prospective, longitudinal SARS-CoV-2 sero-surveillance in schools across England was initiated after the first national lockdown, allowing comparison of child and adult antibody responses over time. Methods: Prospective active serological surveillance in 46 primary schools in England tested for SARS-CoV-2 antibodies during June, July and December 2020. Samples were tested for nucleocapsid (N) and receptor binding domain (RBD) antibodies, to estimate antibody persistence at least 6 months after infection, and for the correlation of N, RBD and live virus neutralising activity. Findings: In June 2020, 1, 344 staff and 835 students were tested. Overall, 11.5% (95%CI: 9.4–13.9) and 11.3% (95%CI: 9.2–13.6; p  = 0.88) of students had nucleoprotein and RBD antibodies, compared to 15.6% (95%CI: 13.7–17.6) and 15.3% (95%CI: 13.4–17.3; p  = 0.83) of staff. Live virus neutralising activity was detected in 79.8% ( n  = 71/89) of nucleocapsid and 85.5% (71/83) of RBD antibody positive children. RBD antibodies correlated more strongly with neutralising antibodies (rs=0.7527; p <0.0001) than nucleocapsid antibodies (rs=0.3698; p <0.0001). A median of 24.4 weeks later, 58.2% (107/184) participants had nucleocapsid antibody seroreversion, compared to 20.9% (33/158) for RBD ( p <0.001). Similar seroreversion rates were observed between staff and students for nucleocapsid ( p  = 0.26) and RBD-antibodies ( p  = 0.43). Nucleocapsid and RBD antibody quantitative results were significantly lower in staff compared to students ( p  = 0.028 and <0.0001 respectively) at baseline, but not at 24 weeks ( p  = 0.16 and p  = 0.37, respectively). Interpretation: The immune response in children following SARS-CoV-2 infection was robust and sustained (>6 months) but further work is required to understand the extent to which this protects against reinfection. Funding: Department for Health and Social Care.